2018
DOI: 10.3390/nu10121960
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Dietary Intake and Physical Activity in Older Adults: A Cross-Sectional Study

Abstract: Background: Evidence shows that diet is associated with physical activity. However, there has been a lack of studies addressing it in a population of older adults. Therefore, the main purpose of this study was to explore associations between various frequencies of dietary intake and physical activity in older adults. Methods: In this cross-sectional study, the participants were 810 older adults aged ≥85. Frequency of dietary intake and the level of physical activity were assessed using the Elderly Diet Index s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Having been diagnosed with chronic diseases was also related to a weak diet in the univariate analysis; however, this association became non-significant after adjusting for the covariates. Similar results were also obtained by other researchers ( 53 ), who showed that dietary intakes could result in different health outcomes when other covariates were involved. This indicates that a holistic approach should be taken when considering the prevention of different health risk factors due to interaction between each of them, which creates an even more significant synergistic risk.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Having been diagnosed with chronic diseases was also related to a weak diet in the univariate analysis; however, this association became non-significant after adjusting for the covariates. Similar results were also obtained by other researchers ( 53 ), who showed that dietary intakes could result in different health outcomes when other covariates were involved. This indicates that a holistic approach should be taken when considering the prevention of different health risk factors due to interaction between each of them, which creates an even more significant synergistic risk.…”
Section: Discussionsupporting
confidence: 90%
“…Another significant inverse association was found between weak diet and PA. Respondents with weak dietary habits were the ones to be the least physically active and not achieving the 150 min/week of PA recommended by the WHO. This association was also found to be the same in other studies ( 8 , 48 , 52 , 53 ) where higher adherence to a healthy diet was associated with higher PA. Children and adolescents with higher levels of PA were found to consume more healthy foods and to like juice, water, milk, dairy products, fruit, and vegetables compared to those with lower PA levels ( 54 ). A cross-sectional study carried by Yang et al ( 55 ) found that participants with a lower BMI and higher PA levels had lower scores in fast food consumption.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Therefore, we used both objective and subjective measures to collect data on older adults’ awareness of and actual physically active and sedentary lifestyles. In addition, although several studies examined the association between physical activity and dietary behavior [12,13], few compared the sedentary behavior patterns of older adults with and without a healthy dietary behavior [14]. We hypothesized that older adults without a healthy diet may engage in less physical activity and more sedentary time than those with a healthy diet.…”
Section: Introductionmentioning
confidence: 99%